Karakterisasi Sifat Listrik Dan Sifat Termal Hidroksiapatit, Fluorhidroksiapatit Dan Fluorapatit - Riano, Riza; Sukaryo, Sulistioso Giat; Sugeng, Bambang; Sari, Yessie Widya; Maddu, Akhiruddin (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
The apatite compound that is often used in medicine and dentistry is hydroxyapatite with the chemical formula Ca10(PO4)6(OH)2. Fluor ions can substitute hydroxyl ions from hydroxyapatite to form crystals with the formula Ca (PO4)6(OH)2-xF2x, with the value of x indicating the index number of hydroxyl groups (OH-) replaced by fluor ions (F-). This study aims to determine the effect of fluor ion substitution on hydroxyapatite on electrical properties and thermal stability. In this study, the hydrothermal method was characterized by X-Ray diffractometer (XRD), Fourier Transform Infra-Red Spectroscopy (FTIR), LCR meter, Thermogravimetry Analysis (DTA), and Differential Thermal Analysis (TGA). The XRD and FTIR analysis results showed that the samples obtained were in the form of hydroxyapatite, fluorhydroxyapatite, and fluorapatite, which was also indicated by the presence of functional groups PO43-, CO32-, and OH- group libration mode at a wavenumber of 740 cm-1. There was a decrease in the lattice parameter a and an increase in the crystal size as the substitution of fluor ions increased. Based on the results of the electrical and thermal properties characterization, fluorapatite has the highest conductivity and better thermal stability when compared to hydroxyapatite and fluohydroxyapatite.Keywords – Fluor, Hydroxyapatite, Hydrothermal, eggshell, Biomaterial